Γδ T cells come to stay: Innate skin memory in the Aldara model. Issue 11 (12th October 2015) - Prinz, Immo; Sandrock, Inga
Abstract : The term immunological memory has long been a trademark restricted to adaptive lymphocytes such as memory B cells and plasma cells as well as memory CD8 + αβ T cells. In recent years, innate lymphocytes such as NK cells have also been shown to adapt to their environment by antigen‐specific expansion and selective survival. However, whether γδ T cells mount comparable memory responses to pathogenic stimuli is less well understood. In this issue of European Journal of Immunology, Hartwig et al. [Eur. J. Immunol. 2015. 45: 3022–3033] identify a subset of IL‐17‐producing γδ T cells that are capable of establishing long‐lived memory in the skin of mice exposed to imiquimod in the Aldara psoriasis model. These γδ T cells uniformly express a Vγ4 + Vδ4 + TCR. They produce IL‐17A/F and persist in the dermis for long periods of time, also at untreated distal sites. Upon secondary challenge, experienced Vγ4 + Vδ4 + cells show enhanced effector functions and mediate exacerbated secondary inflammation. These findings showcase innate γδ T‐cell memory that uses a single conserved public TCR combination. Furthermore, they provide mechanistic insight to the observed psoriatic relapses in patients in response to topical treatment with imiquimod.